Discussion of the technology and research in fuel injectors common rail system - Maskan, Muhammad Haziq; Mohamad Yusuf, Mohamad Wafi; Khalid, Amir; Ishak, Izuan Amin; Zaman, Izzuddin; Sapit, Azwan (Penerbit UTHM, 2017)
Common rail is one of the most important components in a diesel and gasoline direct injection system. It features a high-pressure (100 bar) fuel rail feeding solenoid valves, as opposed to a low-pressure fuel pump feeding unit injectors. Third-generation common rail diesels now feature piezoelectric injectors for increased precision, with fuel pressures up to 2,500 bar. The purpose of this review paper is to investigate the technology and research in fuel injectors common rail system. This review paper focuses on component of common rail injection system, pioneer of common rail injection, characteristics of common rail injection system, method to reduce smoke and NOx emission simultaneously and impact of common rail injection system. Based on our research, it can be concluded that common rail injection gives many benefit such as good for the engine performance, safe to use, and for to reduce the emission of the vehicle. Fuel injection common rail system is the modern technology that must be developed. Nowadays, our earth is polluting by vehicle output such as smoke. If the common rail system is developed, it can reduce the pollution and keep our atmosphere clean and safe.